2002
DOI: 10.1111/j.1432-2277.2002.tb00147.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide-binding-protein as a new and reliable infection marker after kidney transplantation

Abstract: Lipopolysaccharide-binding protein as a new and reliable infection marker after kidney transplantationAbstract The early and reliable differentiation of rejections, viral infections and bacterial infections is one of the main problems after organ transplantation. One promising solution to this problem is the lipopolysaccharide-binding protein (LBP), which is regulated upwards in gram-negative sepsis and related conditions. Therefore, the aim of our study was to explore the diagnostic potential of LBP serum lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 34 publications
0
7
0
1
Order By: Relevance
“…Until now, there have been limited data on LBP serum levels in gram-positive and fungal infections [6,[10][11][12][13]. Opal et al [6] described increased LBP serum levels in patients with grampositive and fungal infections, but LBP serum levels in patients with gram-negative bacteremia were significantly higher.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Until now, there have been limited data on LBP serum levels in gram-positive and fungal infections [6,[10][11][12][13]. Opal et al [6] described increased LBP serum levels in patients with grampositive and fungal infections, but LBP serum levels in patients with gram-negative bacteremia were significantly higher.…”
Section: Discussionmentioning
confidence: 96%
“…One study performed in patients with chronic ambulatory peritoneal dialysis has described elevated LBP serum levels in peritoneal efflux of patients suffering from gram-negative and gram-positive peritonitis [14], but no corresponding LBP serum levels were provided. Kaden et al [10] described elevated LBP serum levels in 2 patients, who had undergone kidney transplantation, with Pneumocystis carinii pneumonia complicated by mycotic superinfection. However, no information on pure or mixed mycotic infections due to common fungus, such as Candida species, were given.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…There have been 2 studies regarding the clinical value of LBP in this context. Kaden et al observed that cytomegalovirus infection is not associated with increased LBP concentrations (21 ), and Heumann and coworkers noted increased LBP concentrations in patients with rheumatic disorders (28 ). By comparison, the percent increases in LBP concentrations calculated for patients with rheumatic disorders (degenerative arthritis, 6.3%; rheumatoid arthritis, 25.8%; reactive arthritis, 46.0%) were lower than the 83.2% increase seen in our IE cohort.…”
Section: Discussionmentioning
confidence: 99%